আত্নজীবন - এছলামাবাদী, মোহাম্মদ মনিরুজ্জমান ১৮৭৫-১৯৫০.; খান, শামসুজ্জামান (ঢাকা : পাঠক সমাবেশ, 2004)
Autobiography of a Bengali Muslim teacher, scholar, and author from Bangladesh.
গ্রন্থপঞ্জিগত নির্দেশিকা অন্তর্ভুক্ত।
Donated By Akbar Ali Khan
In Bengali.
Keywords: Isalāmābādī, Mohāmmada Manirujjāmāna, -- 1875-1950.; Muslim teachers -- Bangladesh -- Biography; Muslim scholars -- Bangladesh -- Biography; Authors, Bengali -- Bangladesh -- Biography; Bengali literature